IN MEMORIAM Fernando Luis González Rey (1949-2019) - Abarca Cordero, Julio César (2021)
It is a descriptive article in homage to Dr. Fernando González Rey, who was a Psychologist considered an eminence for his time, with a cultural-historical approach valued by many Latin Americans. He was the forerunner of the theory of subjectivity and its constitutive-interpretive method. An honor to write and collect information about a great scientist and cancer fighter.